The metaphor of an ensemble: architectural design and skill convergence. (1st January 2012) - D'souza, Newton
This paper describes the significance, conception, and application of skill convergences in architectural design. Using an architectural studio, skill convergences are measured, through students' conception of skills as well as students' application of skills to specific design problems. The metaphor of an ensemble is used as a framework to describe designing as a process of skill convergence, in which multiple skills are involved and applied without a pre-determined hierarchy.